2017
DOI: 10.1016/j.molcel.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphosite within the SH2 Domain of Lck Regulates Its Activation by CD45

Abstract: SUMMARY The Src Family kinase Lck sets a critical threshold for T cell activation because it phosphorylates the TCR complex and the Zap70 kinase. How a T cell controls the abundance of active Lck molecules remains poorly understood. We have identified an unappreciated role for a phosphosite, Y192, within the Lck SH2 domain which profoundly affects the amount of active Lck in cells. Notably, mutation of Y192 blocks critical TCR proximal signaling events and impairs thymocyte development in retrogenic mice. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 59 publications
6
71
1
Order By: Relevance
“…While it is relatively well documented that the conformational states control enzymatic activity, how membrane-bound Lck finds and phosphorylates its substrates is not well understood. For example, the link between phosphorylation state and activity is well established 39 , as well as some interactions of Lck with other proteins 40-43 and lipids 44 Most studies so far have focused on whether or not T cell stimulation results in an ‘activation’ of Lck itself, i.e., whether there is an overall increase of Lck molecules in the open conformation and whether a stable pool of open Lck already exists in resting T cells. However, it is also possible that in the dynamic environment of the inner leaflet of the plasma membrane, Lck switches between open and closed states, as many other types of enzymes do 45-47 .…”
Section: Discussionmentioning
confidence: 99%
“…While it is relatively well documented that the conformational states control enzymatic activity, how membrane-bound Lck finds and phosphorylates its substrates is not well understood. For example, the link between phosphorylation state and activity is well established 39 , as well as some interactions of Lck with other proteins 40-43 and lipids 44 Most studies so far have focused on whether or not T cell stimulation results in an ‘activation’ of Lck itself, i.e., whether there is an overall increase of Lck molecules in the open conformation and whether a stable pool of open Lck already exists in resting T cells. However, it is also possible that in the dynamic environment of the inner leaflet of the plasma membrane, Lck switches between open and closed states, as many other types of enzymes do 45-47 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, such 10-to 20-nm extension of a TCR-pMHC complex under force reduces its size difference from CD45, thus possibly preventing CD45 exclusions from TCRs during TCR initial triggering according to the kinetic segregation model (Davis and van der Merwe, 2006). This might be beneficial for TCR initial triggering because CD45 has been reported to be essential for early TCR proximal signaling by regulating Lck activation (Courtney et al, 2017;Dustin and Depoil, 2011). This hypothesis is actually supported by a recent finding (Cai et al, 2017) that no profound CD45 exclusion is observed on TCR pre-enriched microvillar tips of T cells during the very early stage of TCRs searching for cognate antigens on APCs, whereas, at the later stage of IS formation, CD45 is excluded from TCRs in the center of supramolecular activation clusters (Cai et al, 2017;Chang et al, 2016;Choudhuri et al, 2005).…”
Section: Force-induced Mhc Conformational Changes Facilitate Tcr Antimentioning
confidence: 99%
“…1B), thereby preventing exclusion of CD45 from the region of T cell-APC contacts (36). This may allow CD45 to dephosphorylate the C-terminal tail of Lck, which is required to convert this critical kinase to its active conformation (37). In contrast, CD45 exclusion favors the phosphorylated state of CD3 ITAMs, which promotes T-cell activation (13).…”
Section: Jbc Reviews: Structural Basis Of T-cell Receptor Activationmentioning
confidence: 99%